Adult Wilms with Biphasic Pattern; A Case Report - Mahdi Farzadnia; Mahboobe Karrabi; Hamidreza Ghorbani (Babol University of Medical Sciences, 2021)
Background: Wilmschr('39') tumor, nephroblastoma, is an extremely uncommon kidney tumor of adulthood. We reported a woman with a huge kidney mass diagnosed with nephroblastoma. Case presentation: A 39-year-old female was assessed due to right flank pain. CT scan revealed a mass measuring 128×100 mms involving the upper portion of the right kidney. The patient underwent nephrectomy, and the diagnosis of adult Wilmschr('39') tumor was confirmed based on the morphological and immunohistochemical findings. Conclusion: In adult patients with flank pain and renal mass, the diagnosis of Wilmschr('39') tumor should be pronounced in the absence of histopathologic features of renal cell carcinoma.